Faecalibacterium prausnitzii Strain HTF-F and Its Extracellular Polymeric Matrix Attenuate Clinical Parameters in DSS-Induced Colitis - Rossi, Oriana; Khan, M Tanweer; Schwarzer, Martin; Hudcovic, Tomas; Srutkova, Dagmar; Duncan, Sylvia H; Stolte, Ellen H; Kozakova, Hana; Flint, Harry J; Samsom, Janneke N; Harmsen, Hermie J M; Wells, Jerry M (PLoS One, 2015)
A decrease in the abundance and biodiversity of intestinal bacteria within the Firmicutes phylum has been associated with inflammatory bowel disease (IBD). In particular, the anti-inflammatory bacterium Faecalibacterium prausnitzii, member of the Firmicutes phylum and one of the most abundant species in healthy human colon, is underrepresented in the microbiota of IBD patients. The aim of this study was to investigate the immunomodulatory properties of F. prausnitzii strain A2-165, the biofilm forming strain HTF-F and the extracellular polymeric matrix (EPM) isolated from strain HTF-F. For this purpose, the immunomodulatory properties of the F. prausnitzii strains and the EPM were studied in vitro using human monocyte-derived dendritic cells. Then, the capacity of the F. prausnitzii strains and the EPM of HTF-F to suppress inflammation was assessed in vivo in the mouse dextran sodium sulphate (DSS) colitis model. The F. prausnitzii strains and the EPM had anti-inflammatory effects on the clinical parameters measured in the DSS model but with different efficacy. The immunomodulatory effects of the EPM were mediated through the TLR2-dependent modulation of IL-12 and IL-10 cytokine production in antigen presenting cells, suggesting that it contributes to the anti-inflammatory potency of F. prausnitzii HTF-F. The results show that F. prausnitzii HTF-F and its EPM may have a therapeutic use in IBD.
Keywords: antigeny povrchové; Animals; Intestinal Mucosa; Female; Phenotype; Cytokines; Toll-Like Receptor 2; slezina; ženské pohlaví; kolitida; Dendritic Cells; dendritické buňky; cytokiny; Inflammatory Bowel Diseases; Transcription, Genetic; lymfatické uzliny; Inflammation Mediators; síran dextranu; Mice; Dextran Sulfate; forkhead transkripční faktory; myši; extracelulární matrix; genetická transkripce; Forkhead Transcription Factors; toll-like receptor 2; modely nemocí na zvířatech; Colitis; Spleen; Disease Models, Animal; Extracellular Matrix; Lymph Nodes; idiopatické střevní záněty; mediátory zánětu; fenotyp; zvířata; Antigens, Surface; Ruminococcus; střevní sliznice